Synthesis Of Modified Coffee Ground Adsorbents To Remove Malachite Green Dyes - Sinnaiah, Roshini (Universiti Sains Malaysia, 2021)
Coffee waste treated with potassium hydroxide (KOH) and hydrochloric acid (HCl) was used as a low-cost adsorbent for the adsorption of malachite green (MG) dye solution. A preliminary study was carried out and the coffee ground treated with KOH and HCl with the heat treatment showed the highest MG dye removal percentage of 96.14 % and 23.51 mg/g of adsorption capacity of MCG. Optimization of the operating parameters for preparation of modified coffee ground adsorbent for the removal of MG dye molecules using central composite design (CCD). A total of 20 set of experiment were simulated to get the optimum process conditions of this study. Based on the RSM results, the optimum conditions for all the parameters were successfully identified such at pH 7.3, contact time of 6.9 hours and adsorbent dosage of 0.2 g while the maximum percentage of MG dye removal obtained from the optimized condition was 85.02 % and adsorption capacity of 1.65 mg/g respectively. The CG samples has been characterized using by Brunauer–Emmett–Teller (BET), Fourier transform infrared spectroscopic (FTIR), scanning electron microscopic (SEM) and CHNS analyser. MCG showed a better characterization result compared to untreated CG. The effect of initial concentration of dye, contact time, solution pH and adsorbent dosage for adsorption of MG dye has been investigated for equilibrium and kinetic study. Freundlich isotherm model was found perfectly fitted model to explain the adsorption behaviour of MG adsorption and pseudo second order model plot was best fitted with the experimental observation by using linear regression analysis. This study shows that CG waste showed a promising and efficient low cos adsorbent for the removal of MG dye solution.